PROMOTING INDONESIAN TOURISM TO CHINESE TOURISTS THROUGH JOURNALISM STRATEGIES IN WECHAT - Yuniarto, Hendy (Sanata Dharma University, 2017)
Indonesia is one of the top ten destinations for Chinese people. In fact, Chinese tourists contributed the highest number of foreign tourists to Indonesia. The innovative access to information facilitated them to plan itinerary in Indonesia. The Indonesian government who aimed at increasing Chinese tourists can implement digital tools. This brief study elaborates the use of journalism to review destinations which were disseminated through Wechat. Various destinations in Indonesia can be informed to more than 800 million of Wechat users. The reviews of a tourism destination are not limited to general or popular destinations, but also to new destinations that have not been known widely. The news structure is divided into 6 sections, including location details, the history, the attraction, how to get to the place, useful information, and the cost. Some obstacles related to translation and the dissemination of the news can be solved by working with some parties to promote this strategy.DOI: https://doi.org/10.24071/ijhs.2017.010111